Skupnost in kakovost življenja - Mandič, Srna (Teorija in praksa, 2018)
The article examines the ambiguity of the concept of community, and in reviewing the literature, it systematically addresses the wide spectre of its meanings, from those proposed by the most influential early theoreticians to modern conceptualisations marked by the explosion of a variety of new manifestations of community and community practices. Our aim is to identify the key layers of the meaning of community and thematise their meaning from several aspects. First, in regard to the modern differentiated and segmented social science we find that these layers of meaning appear in a variety of numbers and in different combinations, which is why a coherent and theoretically substantiated understanding of community requires the connection to a narrower framework limited to a coherent corpus of knowledge constituted by societal, territorial or policy dimensions. Second, our aim is to identify the presence of these layers of the meaning of community in the concepts of the quality of life and well-being, and in their operationalisation for the needs of empirical research, with highlighting the problem of coherent and theoretically grounded interpretation of empirical results. Finally, we establish the specific characteristics of of modern communities which, as opposed to traditional communities that are based on tradition, are often based on innovation, such as new models of making connections, collective action and also participation in public policies.
Keywords: Blaginja; Community; Družbeni kazalci; Kakovost življenja; Quality of life; Skupnost; Social indicators; Welfare